PERSEPSI ANGGOTA TERHADAP PELAYANAN KUD MAKARTI DI DESA SUNGAI KERANJI KABUPATEN KUANTAN SINGINGI - Rosnita '; Andi Nurbai; Eri Sayamar (Jurnal Sagu, 2004)
Purpose of this research was to know the level of service of KUD to farmer of coconut of great farm at one blowservice of KUD to all its member. Result of research indicate that for service of unit of waserda have averagevalue 79,71 which is the Included in the category of good service. Service of unit ofis effort medium produce toshow average value 57,14 included in category of service of sufficient. To service of unit of marlceting of yieldup the ghost have average value 80 .score in category of good service. Result of calculation from sale and buy is72,13 gratuity, score that equal to 72,13 gratuity of volume of effort KUD have earned accessed by all itsmember and had also fulfilled category of good service.